Location and contract pricing of distributed generation using a genetic algorithm - Lopez-Lezama, Jesus Maria; Contreras, Javier; Padilha-Feltrin, Antonio [UNESP] (Elsevier B.V., 2012)
This paper presents an approach based on a specialized genetic algorithm (GA) to determine the location and contract pricing of dispatchable distributed generation (DG) units in distribution systems. The proposed approach is based on a nonlinear bilevel programming framework that involves the interests of two different agents: the DG owner who procures the maximization of the profits obtained from the energy sales, and the Distribution Company (DisCo), which procures the minimization of the payments incurred in attending the forecasted demand. To meet the forecasted demand the DisCo can purchase energy either from the wholesale energy market or from the DG units within its network. The proposed GA determines both the location and contract pricing of the DG units that would render maximum profits to the DG owner, subject to the minimization of payments procured by the DisCo. To show the effectiveness of the proposed approach, several tests were carried out on a modified IEEE 34-bus and 85-bus distribution networks. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Distributed generation; Genetic algorithms; Nonlinear bilevel programming; Distribution systems